Development of IgE microarray assays for classification of allergic individuals - Hamed, Aljali (2016)
Allergic reactions are pathological immune reactions against common, harmless environmental proteins, termed “allergens”. Type I hypersensitivity reactions are mediated by IgE antibodies; these reactions are the most prevalent, affecting all ages and both genders to almost the same extent. This form of allergic reaction is distributed widely affecting more than 25% of the population in the industrial world. The increased incidence of IgE-mediated allergy is thought to be a combination of environmental and genetic factors, each account for about 50%. The effects associated with this disease may reduce quality of life, daily activities, and in some cases threaten life, hence affecting work and leisure time, increasing healthcare and medication costs.